EFFECTS OF ISOLATED AND COMBINED EFFECTS OF AEROBIC DANCING AND RESISTANCE TRAINING ON SYSTOLIC BLOOD PRESSURE OF TYPE-2 DIABETIC PATIENTS - Maniazhagu, D. (International Journal of Research -GRANTHAALAYAH, 2017)
The purpose of study was to find out the effects of isolated and combined effects of aerobic dancing and resistance training on systolic blood pressure of type-2 diabetic patients. To achieve the purpose of the study, 60 type 2 diabetic patients from Karaikudi town, Sivaganga District, Tamilnadu were selected as subject at random. The study was formulated as pre and posttest random group design, in which sixty subject were divided into four equal groups. The experimental group-1 (n=15, AD, experimental group-2 (n=15, RT), experimental group – 3 (n=15, COM-T) and group-4 (n=15, CG) served as a control group. In this study, three training programme were adopted as independent variable, i.e., aerobic dancing, resistance training and combined training. The systolic blood pressure was chosen as dependent variable. The collected pre and post data was critically analyzed with apt statistical tool of analysis of co-variance. The Scheffe’s post hoc test was used to find out pair-wise comparisons between groups. The results of the present study proved that the three training interventions have produced significantly altered on systolic blood pressure.